Inter personal violence-related facial injuries: a 10-year survey - Coulibaly Toua Antoine; Béogo Rasmané; Traoré Ibraïma; Kohoun Héra Michel; Ili Biévianda Vincent (EDP Sciences, 2018)
Introduction: Interpersonal violence (IPV) has emerged as a worldwide health problem affecting predominantly the face. Patients and methods: This study reports the characteristics of violence, victims and injuries in IPV-related facial injuries patients, in a 10-year survey, in a tertiary hospital of Burkina Faso. Results: Patients' age ranged from 11 to 75 years (mean 31 years) and 58.2% of the patients were aged between 20 and 39 years. There were 74 males and females 24 giving a male-to-female ratio of 3.1:1. The circumstances of injuries were brawls (80.6%) consisting mostly in facial blows, and hold-ups (19.4%). Fractures involving predominantly the mandible or the zygomatic complex were the most common injury, accounting for 53.2%. Soft tissues injuries accounted for 37.2% and dental trauma for 9.2%. In 27.5% of the patients, extra facial injuries were encountered, dominated by cerebral trauma and limb fractures. Conclusion: In this study, IPV-related facial injuries are mostly mandibular or zygomatic fractures in young and males adults involved in brawls. These findings command strategies for prevention of violence in this specific group.